The psychological impact of the COVID-19 pandemic on the Sudanese healthcare workers in quarantine centers: a cross-sectional study 2020–2021 - Malaz Hassan Dafaalla Idrees; Moez Mohammed Ibrahim Bashir (Middle East Current Psychiatry, 2023)
Abstract Background After its emergence in Wuhan in December 2019, the COVID-19 virus disseminated around the globe creating an incredible panic and outweighing the healthcare system’s capacities. As a result of this hazardous situation, healthcare workers were placed at an unprecedented challenge making them vulnerable to a wide spectrum of mental health issues including anxiety and depression. This was a cross-sectional health facility-based study aiming to explore the psychological impact of the COVID-19 pandemic on Sudanese healthcare workers in COVID-19 treatment centers. Convenience sampling was applied. And two-part self-administered online questionnaire was used: the first part consisted of the demographic data and concerns related to COVID-19, and the second part consisted of the Hospital Anxiety and Depression Scale (HADS) standardized questionnaire. Ethical clearance was obtained from the Ministry of Health. Results One-hundred thirty-three healthcare workers of different job titles were enrolled in this study. A total of 54% were females, and 46% were males. Most of the participants had borderline depression (44%) or anxiety scores (47%). Females had significantly a higher mean anxiety score than males. There was no significant difference between participants with and without chronic disease on both anxiety and depression scores. Conclusions Healthcare workers at the forefront of the fight against COVID-19 pandemic are facing critical mental health challenges. An immediate intervention from the decision-makers is needed to mitigate this deleterious impact and to strengthen the healthcare system’s capacity in the face of healthcare emergencies in general.